Three essays in finance - Phua, Kenny Jing Wen (2018)
We find evidence that the leadership of overconfident chief executive officers (CEOs) induces stakeholders to take actions that contribute to the leader’s vision. By being intentionally overexposed to the idiosyncratic risk of their firms, overconfident CEOs exhibit a strong belief in their firms’ prospects. This belief attracts suppliers beyond the firm’s observable expansionary corporate activities. Overconfident CEOs induce more supplier commitments including greater relationship-specific investment and longer relationship duration. Overconfident CEOs also induce stronger labor commitments as employees exhibit lower turnover rates and greater ownership of company stock in benefit plans. We examine how learning from colleagues affects security analyst forecast outcomes. We represent the brokerage house as an information network of analysts connected through industry overlaps in their coverage portfolios. Analysts who are more centrally connected in their brokerage network produce more accurate forecast estimates and generate more influential forecast revisions. Consistent with learning, more central analysts tend to unwind their colleagues’ recent forecast errors in their own forecast revisions. Benefits from inter-colleague information exchange accrue to all analysts at the same brokerage. I map an information-based network of the equity market by linking stocks that are jointly covered by sell-side equity analysts. I exploit a topological feature of networks—the friendship paradox—and show that complementarities in information production can generate information diffusion. Particularly, stock returns of firms are led by those of network neighbors. This effect is robust to adjustments for industry effects, and is not explained by firm characteristics. There are no return reversals in the longer term.